Combined therapy of prednisone and mTOR inhibitor sirolimus for treating retroperitoneal fibrosis. Issue 5 (31st January 2023) - Gao, Hui; Liu, Shibo; Mai, Yuanbang; Wang, Yuying; Zhang, Xuewu; Zheng, Shufen; Luo, Chenghua; Pan, Cuiping
Abstract : Objectives: Retroperitoneal fibrosis (RPF) is a rare autoimmune disease with fibrous tissue growth and inflammation in retroperitoneum. Its current treatments involve long-term uptake of glucocorticoids (e.g., prednisone) for controlling inflammation; however, side effects are common. We strived for an improved therapy for fibrosis remission while reducing side effects. Methods: We surveyed gene-disease-drug databases and discovered that mammalian target of rapamycin (mTOR) was a key signalling protein in RPF and the mTOR inhibitor compound sirolimus affected many RPF pathways. We designed a therapy combining a gradual reduction of prednisone with a long-term, stable dosage of sirolimus. We then implemented a single-arm clinical trial and assessed the effects in eight RPF patients at 0, 12 and 48 weeks of treatment by measuring fibrous tissue mass by CT, markers of inflammation and kidney functions by lab tests, immune cell profiles by flow cytometry and plasma inflammatory proteins by Olink proteomics. Results: With the combined therapy, fibrous tissue shrunk about by half, markers of acute inflammation reduced by 70% and most patients with abnormal kidney functions had them restored to normal range. Molecularly, fibrosis-related T cell subsets, including TH 2, TH 17 and circulating TFH cells, were reduced and tumour necrosis factor and related cytokines restored to healthy levels. No severe long-term side effects were observed. Conclusions: Our combined therapy resulted in significant fibrosis remission and an overall regression of the immune system towards healthy states, while achieving good tolerance. We concluded that this new therapy had the potential to replace the steroid monotherapy for treating RPF.